SAT0628 High Prevalence of Ultrasound Verified Enthesitis in Patients with Inflammatory Bowel Disease with or Without Spondylarthritis. (9th June 2015) - Husic, R.; Lackner, A.; Ficjan, A.; Kump, P.; Hoegenauer, C.; Graninger, W.; Dejaco, C.
Abstract : Background: Inflammatory bowel disease (IBD) is closely associated with spondylarthritis (SpA). Enthesitis is an important feature of SpA but may be clinically silent in a high proportion of patients. Objectives: The aim of this study was to compare the prevalence of ultrasound (US) verified enthesitis in IBD patients with and without SpA, patients with irritable bowel syndrome (IBS) and healthy controls (HC). Methods: We prospectively recruited IBD patients with or without SpA, patients with IBS and HC. Clinical assessments included demographics, comorbidities, IBD symptoms, BMI, sport activities and a musculoskeletal clinical examination. Ultrasound examination was performed by 1 of 2 independent investigators, blinded to clinical results, at 12 entheses: bilaterally triceps, lateral epicondyles, distal insertion of quadriceps, proximal and distal insertion of patellar tendon, distal insertion of Achilles tendon and plantar fascia using an Esaote MyLab Twice ultrasound device with 18-MHz linear transducer. The following abnormalities were scored according to the Madrid Ankylosing Spondylitis Enthesitis Index (MASEI), and the Glasgow Ultrasound Enthesitis Scoring System (GUSS) as appropriate: Power Doppler (PD) changes, enthesophytes, erosions, enthesal thickening, bursitis and structural abnormalities. Statistical analysis was performed using SPSS v22 and we used the Mann Whitney U test and the Chi square test for comparisons. Inter-reader agreement between ultrasound investigators was tested using the Intra-class correlation coefficient (ICC). Results: We included 33 IBD patients without SpA [66.7% male; median age 44 years (range 19-62), median ESR 9mm/h (range 1-45), CRP 3.5 mg/l (0.6-39.2), anti-TNF therapy in 45.5%], 14 IBD patients with SpA [71.4% male, age 45 years (21-56), ESR 10mm/h (3-25), CRP 3.0mg/l (0.1-41.0), anti-TNF therapy in 71.4%], 26 IBS patients [26.9% male (p<0.05 compared to IBD patients without or with SpA), age 41 (18-65)] and 18 HC [27.8% male (p<0.05 compared to IBD patients without or with SpA), age 43 (21-58)]. Higher MASEI scores were found in patients with IBD without SpA [median 21.0 range (8.0-53.0)] and IBD associated SpA [33.0 (8-50)] than in IBS patients [10.5 (0-42.0)-p<0.001 for both comparison] and HC [12.0 (2.0-38.0)-p<0.01 for both comparisons]. Similar results were observed for the GUSS scores. Enthesophyte subscores were highest in IBD patients with SpA [median 11.5 (range 0-26.0)] as compared to IBD without SpA [7 (2-28)], IBS [5 (0-25)] and HC groups [6.5 (0-21), p<0.05 for all comparisons]. Positive PD was more commonly observed in patients with IBD without SpA [n=22 (66.7%)] and IBD with SpA [n=9 (64.3%)] compared to IBS patients [n=5 (19. 2%)] and HC [n=4 (22.2%), p<0.05 for all comparisons]. Erosion were more common in patient with IBD without SpA [18 (54.5%)], IBD with SpA [11 (78. 6%)] and IBS patienta [10 (38. 5%)] compared to HC [2 (11. 1%), p<0.05 for all comparisons]. No association was found between US results and clinical variables. The intra-reader agreement was good [ICC 0.89 (0.52 to 0.98)]. Conclusions: Ultrasound verified enthesitis is more common in patients with IBD with or without SpA as compared to patients with IBS or HC. Disclosure of Interest: None declared